Treatment Patterns for Distal Radius Fractures Before and After Appropriate Use Criteria Adoption. (November 2022) - Samade, Richard; Zaki, Omar; Farrell, Nolan; Farrar, Nicholas; Goyal, Kanu S.
Background: The purpose of this study was to determine agreement with the American Academy of Orthopaedic Surgery Appropriate Use Criteria (AUC) for distal radius fractures (DRFs), before and after their adoption, and secondarily determine predictors of operative management. Methods: A single-institution retrospective cohort study comparing patients treated either nonoperatively (115 patients) or operatively (767 patients) for DRFs between May 1, 2008, and May 1, 2018, by 8 hand surgeons was performed. Data included demographics, injury characteristics, DRF radiographic measurements, treatment rendered, and their appropriateness according to the AUC. Statistical testing used the Fisher and χ 2 tests, t test, and multiple variable logistic regression, with a significance level of .05. Results: Overall, there was a significant increase in AUC agreement for operatively treated DRFs (82.7%-89.3%, P = .01), but no difference in agreement for nonoperatively treated DRFs (12.5%-10.7%, P = .77). Age <80 years, AO classes other than B, intra-articular displacement >1 mm, radial inclination <18°, high-energy mechanism of injury, and greater than 1 week to treatment were independent predictors of operative treatment. The area under the curve for the validated regression model using the aforementioned predictors was 0.82. Conclusion: Agreement with AUC for DRFs increased after its adoption for operatively treated, but not for nonoperatively treated, fractures. In addition, a predictive model for operative treatment was developed and validated. Future studies may benefit from further model refinement and testing in other patient cohorts.